Equine mesenchymal stem cells from bone marrow, adipose tissue and umbilical cord: immunophenotypic characterization and differentiation potential - Barberini, Danielle Jaqueta (BioMed Central, 2014)
INTRODUCTION: Studies with mesenchymal stem cells (MSCs) are increasing due to their immunomodulatory, anti-inflammatory and tissue regenerative properties. However, there is still no agreement about the best source of equine MSCs for a bank for allogeneic therapy. The aim of this study was to evaluate the cell culture and immunophenotypic characteristics and differentiation potential of equine MSCs from bone marrow (BM-MSCs), adipose tissue (AT-MSCs) and umbilical cord (UC-MSCs) under identical in vitro conditions, to compare these sources for research or an allogeneic therapy cell bank. METHODS: The BM-MSCs, AT-MSCs and UC-MSCs were cultured and evaluated in vitro for their osteogenic, adipogenic and chondrogenic differentiation potential. Additionally, MSCs were assessed for CD105, CD44, CD34, CD90 and MHC-II markers by flow cytometry, and MHC-II was also assessed by immunocytochemistry. To interpret the flow cytometry results, statistical analysis was performed using ANOVA. RESULTS: The harvesting and culturing procedures of BM-MSCs, AT-MSCs and UC-MSCs were feasible, with an average cell growth until the third passage of 25 days for BM-MSCs, 15 days for AT-MSCs and 26 days for UC-MSCs. MSCs from all sources were able to differentiate into osteogenic (after 10 days for BM-MSCs and AT-MSCs and 15 days for UC-MSCs), adipogenic (after 8 days for BM-MSCs and AT-MSCs and 15 days for UC-MSCs) and chondrogenic (after 21 days for BM-MSCs, AT-MSCs and UC-MSCs) lineages. MSCs showed high expression of CD105, CD44 and CD90 and low or negative expression of CD34 and MHC-II. The MHC-II was not detected by immunocytochemistry techniques in any of the MSCs studied. CONCLUSIONS: The BM, AT and UC are feasible sources for harvesting equine MSCs, and their immunophenotypic and multipotency characteristics attained minimal criteria for defining MSCs. Due to the low expression of MHC-II by MSCs, all of the sources could be used in clinical trials involving allogeneic therapy in horses. However, the BM-MSCs and AT-MSCs showed fastest ‘‘in vitro’’ differentiation and AT-MSCs showed highest cell growth until third passage. These findings suggest that BM and AT may be preferable for cell banking purposes.